# Strict inequality on the natural numbers

Content created by Fredrik Bakke, Egbert Rijke, Julian KG, Victor Blanchi, fernabnor, louismntnu and malarbol.

Created on 2023-04-08.

module elementary-number-theory.strict-inequality-natural-numbers where

Imports
open import elementary-number-theory.addition-natural-numbers
open import elementary-number-theory.inequality-natural-numbers
open import elementary-number-theory.natural-numbers

open import foundation.action-on-identifications-functions
open import foundation.cartesian-product-types
open import foundation.coproduct-types
open import foundation.decidable-types
open import foundation.dependent-pair-types
open import foundation.empty-types
open import foundation.function-types
open import foundation.functoriality-coproduct-types
open import foundation.identity-types
open import foundation.negated-equality
open import foundation.negation
open import foundation.propositions
open import foundation.transport-along-identifications
open import foundation.unit-type
open import foundation.universe-levels


## Definition

### The standard strict inequality on the natural numbers

le-ℕ-Prop : ℕ → ℕ → Prop lzero
le-ℕ-Prop m zero-ℕ = empty-Prop
le-ℕ-Prop zero-ℕ (succ-ℕ m) = unit-Prop
le-ℕ-Prop (succ-ℕ n) (succ-ℕ m) = le-ℕ-Prop n m

le-ℕ : ℕ → ℕ → UU lzero
le-ℕ n m = type-Prop (le-ℕ-Prop n m)

is-prop-le-ℕ : (n : ℕ) → (m : ℕ) → is-prop (le-ℕ n m)
is-prop-le-ℕ n m = is-prop-type-Prop (le-ℕ-Prop n m)

infix 30 _<-ℕ_
_<-ℕ_ = le-ℕ


## Properties

### Concatenating strict inequalities and equalities

concatenate-eq-le-eq-ℕ :
{x y z w : ℕ} → x ＝ y → le-ℕ y z → z ＝ w → le-ℕ x w
concatenate-eq-le-eq-ℕ refl p refl = p

concatenate-eq-le-ℕ :
{x y z : ℕ} → x ＝ y → le-ℕ y z → le-ℕ x z
concatenate-eq-le-ℕ refl p = p

concatenate-le-eq-ℕ :
{x y z : ℕ} → le-ℕ x y → y ＝ z → le-ℕ x z
concatenate-le-eq-ℕ p refl = p


### Strict inequality on the natural numbers is decidable

is-decidable-le-ℕ :
(m n : ℕ) → is-decidable (le-ℕ m n)
is-decidable-le-ℕ zero-ℕ zero-ℕ = inr id
is-decidable-le-ℕ zero-ℕ (succ-ℕ n) = inl star
is-decidable-le-ℕ (succ-ℕ m) zero-ℕ = inr id
is-decidable-le-ℕ (succ-ℕ m) (succ-ℕ n) = is-decidable-le-ℕ m n


### If m < n then n must be nonzero

is-nonzero-le-ℕ : (m n : ℕ) → le-ℕ m n → is-nonzero-ℕ n
is-nonzero-le-ℕ m .zero-ℕ () refl


### Any nonzero natural number is strictly greater than 0

le-is-nonzero-ℕ : (n : ℕ) → is-nonzero-ℕ n → le-ℕ zero-ℕ n
le-is-nonzero-ℕ zero-ℕ H = H refl
le-is-nonzero-ℕ (succ-ℕ n) H = star


### No natural number is strictly less than zero

contradiction-le-zero-ℕ :
(m : ℕ) → (le-ℕ m zero-ℕ) → empty


### No successor is strictly less than one

contradiction-le-one-ℕ :
(n : ℕ) → le-ℕ (succ-ℕ n) 1 → empty


### The strict inequality on the natural numbers is anti-reflexive

anti-reflexive-le-ℕ : (n : ℕ) → ¬ (n <-ℕ n)
anti-reflexive-le-ℕ zero-ℕ ()
anti-reflexive-le-ℕ (succ-ℕ n) = anti-reflexive-le-ℕ n


### If x < y then x ≠ y

neq-le-ℕ : {x y : ℕ} → le-ℕ x y → x ≠ y
neq-le-ℕ {zero-ℕ} {succ-ℕ y} H = is-nonzero-succ-ℕ y ∘ inv
neq-le-ℕ {succ-ℕ x} {succ-ℕ y} H p = neq-le-ℕ H (is-injective-succ-ℕ p)


### The strict inequality on the natural numbers is antisymmetric

antisymmetric-le-ℕ : (m n : ℕ) → le-ℕ m n → le-ℕ n m → m ＝ n
antisymmetric-le-ℕ (succ-ℕ m) (succ-ℕ n) p q =
ap succ-ℕ (antisymmetric-le-ℕ m n p q)


### The strict inequality on the natural numbers is transitive

transitive-le-ℕ : (n m l : ℕ) → (le-ℕ n m) → (le-ℕ m l) → (le-ℕ n l)
transitive-le-ℕ zero-ℕ (succ-ℕ m) (succ-ℕ l) p q = star
transitive-le-ℕ (succ-ℕ n) (succ-ℕ m) (succ-ℕ l) p q =
transitive-le-ℕ n m l p q


### A sharper variant of transitivity

transitive-le-ℕ' :
(k l m : ℕ) → (le-ℕ k l) → (le-ℕ l (succ-ℕ m)) → le-ℕ k m
transitive-le-ℕ' zero-ℕ zero-ℕ m () s
transitive-le-ℕ' (succ-ℕ k) zero-ℕ m () s
transitive-le-ℕ' zero-ℕ (succ-ℕ l) zero-ℕ star s =
transitive-le-ℕ' (succ-ℕ k) (succ-ℕ l) zero-ℕ t s =
transitive-le-ℕ' zero-ℕ (succ-ℕ l) (succ-ℕ m) star s = star
transitive-le-ℕ' (succ-ℕ k) (succ-ℕ l) (succ-ℕ m) t s =
transitive-le-ℕ' k l m t s


### The strict inequality on the natural numbers is linear

linear-le-ℕ : (x y : ℕ) → (le-ℕ x y) + ((x ＝ y) + (le-ℕ y x))
linear-le-ℕ zero-ℕ zero-ℕ = inr (inl refl)
linear-le-ℕ zero-ℕ (succ-ℕ y) = inl star
linear-le-ℕ (succ-ℕ x) zero-ℕ = inr (inr star)
linear-le-ℕ (succ-ℕ x) (succ-ℕ y) =
map-coproduct id (map-coproduct (ap succ-ℕ) id) (linear-le-ℕ x y)


### n < m if and only if there exists a nonzero natural number l such that n + l = m

subtraction-le-ℕ :
(n m : ℕ) → le-ℕ n m → Σ ℕ (λ l → (is-nonzero-ℕ l) × (l +ℕ n ＝ m))
subtraction-le-ℕ zero-ℕ m p = pair m (pair (is-nonzero-le-ℕ zero-ℕ m p) refl)
subtraction-le-ℕ (succ-ℕ n) (succ-ℕ m) p =
pair (pr1 P) (pair (pr1 (pr2 P)) (ap succ-ℕ (pr2 (pr2 P))))
where
P : Σ ℕ (λ l' → (is-nonzero-ℕ l') × (l' +ℕ n ＝ m))
P = subtraction-le-ℕ n m p

le-subtraction-ℕ : (n m l : ℕ) → is-nonzero-ℕ l → l +ℕ n ＝ m → le-ℕ n m
le-subtraction-ℕ zero-ℕ m l q p =
tr (λ x → le-ℕ zero-ℕ x) p (le-is-nonzero-ℕ l q)
le-subtraction-ℕ (succ-ℕ n) (succ-ℕ m) l q p =
le-subtraction-ℕ n m l q (is-injective-succ-ℕ p)


### Any natural number is strictly less than its successor

succ-le-ℕ : (n : ℕ) → le-ℕ n (succ-ℕ n)
succ-le-ℕ zero-ℕ = star
succ-le-ℕ (succ-ℕ n) = succ-le-ℕ n


### The successor function preserves strict inequality on the right

preserves-le-succ-ℕ :
(m n : ℕ) → le-ℕ m n → le-ℕ m (succ-ℕ n)
preserves-le-succ-ℕ m n H =
transitive-le-ℕ m n (succ-ℕ n) H (succ-le-ℕ n)


### Concatenating strict and nonstrict inequalities

concatenate-leq-le-ℕ :
{x y z : ℕ} → x ≤-ℕ y → le-ℕ y z → le-ℕ x z
concatenate-leq-le-ℕ {zero-ℕ} {zero-ℕ} {succ-ℕ z} H K = star
concatenate-leq-le-ℕ {zero-ℕ} {succ-ℕ y} {succ-ℕ z} H K = star
concatenate-leq-le-ℕ {succ-ℕ x} {succ-ℕ y} {succ-ℕ z} H K =
concatenate-leq-le-ℕ {x} {y} {z} H K

concatenate-le-leq-ℕ :
{x y z : ℕ} → le-ℕ x y → y ≤-ℕ z → le-ℕ x z
concatenate-le-leq-ℕ {zero-ℕ} {succ-ℕ y} {succ-ℕ z} H K = star
concatenate-le-leq-ℕ {succ-ℕ x} {succ-ℕ y} {succ-ℕ z} H K =
concatenate-le-leq-ℕ {x} {y} {z} H K


### If m < n then n ≰ m

contradiction-le-ℕ : (m n : ℕ) → le-ℕ m n → ¬ (n ≤-ℕ m)
contradiction-le-ℕ zero-ℕ (succ-ℕ n) H K = K


### If n ≤ m then m ≮ n

contradiction-le-ℕ' : (m n : ℕ) → n ≤-ℕ m → ¬ (le-ℕ m n)


### If m ≮ n then n ≤ m

leq-not-le-ℕ : (m n : ℕ) → ¬ (le-ℕ m n) → n ≤-ℕ m
leq-not-le-ℕ zero-ℕ zero-ℕ H = star
leq-not-le-ℕ zero-ℕ (succ-ℕ n) H = ex-falso (H star)
leq-not-le-ℕ (succ-ℕ m) zero-ℕ H = star
leq-not-le-ℕ (succ-ℕ m) (succ-ℕ n) H = leq-not-le-ℕ m n H


### If x < y then x ≤ y

leq-le-ℕ :
(x y : ℕ) → le-ℕ x y → x ≤-ℕ y
leq-le-ℕ zero-ℕ (succ-ℕ y) H = star
leq-le-ℕ (succ-ℕ x) (succ-ℕ y) H = leq-le-ℕ x y H


### If x < y + 1 then x ≤ y

leq-le-succ-ℕ :
(x y : ℕ) → le-ℕ x (succ-ℕ y) → x ≤-ℕ y
leq-le-succ-ℕ zero-ℕ y H = star
leq-le-succ-ℕ (succ-ℕ x) (succ-ℕ y) H = leq-le-succ-ℕ x y H


### If x < y then x + 1 ≤ y

leq-succ-le-ℕ :
(x y : ℕ) → le-ℕ x y → leq-ℕ (succ-ℕ x) y
leq-succ-le-ℕ zero-ℕ (succ-ℕ y) H = star
leq-succ-le-ℕ (succ-ℕ x) (succ-ℕ y) H = leq-succ-le-ℕ x y H


### If x ≤ y then x < y + 1

le-succ-leq-ℕ :
(x y : ℕ) → leq-ℕ x y → le-ℕ x (succ-ℕ y)
le-succ-leq-ℕ zero-ℕ zero-ℕ H = star
le-succ-leq-ℕ zero-ℕ (succ-ℕ y) H = star
le-succ-leq-ℕ (succ-ℕ x) (succ-ℕ y) H = le-succ-leq-ℕ x y H


### x ≤ y if and only if (x ＝ y) + (x < y)

eq-or-le-leq-ℕ :
(x y : ℕ) → leq-ℕ x y → ((x ＝ y) + (le-ℕ x y))
eq-or-le-leq-ℕ zero-ℕ zero-ℕ H = inl refl
eq-or-le-leq-ℕ zero-ℕ (succ-ℕ y) H = inr star
eq-or-le-leq-ℕ (succ-ℕ x) (succ-ℕ y) H =
map-coproduct (ap succ-ℕ) id (eq-or-le-leq-ℕ x y H)

eq-or-le-leq-ℕ' :
(x y : ℕ) → leq-ℕ x y → ((y ＝ x) + (le-ℕ x y))
eq-or-le-leq-ℕ' x y H = map-coproduct inv id (eq-or-le-leq-ℕ x y H)

leq-eq-or-le-ℕ :
(x y : ℕ) → ((x ＝ y) + (le-ℕ x y)) → leq-ℕ x y
leq-eq-or-le-ℕ x .x (inl refl) = refl-leq-ℕ x
leq-eq-or-le-ℕ x y (inr l) = leq-le-ℕ x y l


### If x ≤ y and x ≠ y then x < y

le-leq-neq-ℕ : {x y : ℕ} → x ≤-ℕ y → x ≠ y → le-ℕ x y
le-leq-neq-ℕ {zero-ℕ} {zero-ℕ} l f = ex-falso (f refl)
le-leq-neq-ℕ {zero-ℕ} {succ-ℕ y} l f = star
le-leq-neq-ℕ {succ-ℕ x} {succ-ℕ y} l f =
le-leq-neq-ℕ {x} {y} l (λ p → f (ap succ-ℕ p))